Prinsip Dasar dan Batasan-Batasan dalam Aktivitas Ekonomi Islam - Akbar, Aziz; Robi'in, Muhammad (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2022)
Mu'amalah is the activity of arranging matters related to the way of life of fellow human beings to meet their daily needs. Mu'amalah aims to provide convenience in fulfilling the necessities of life, to understand each other between sellers and buyers, to help each other, and to strengthen ties of friendship between fellow believers. Even so, not all of these goals can be implemented in a syar'i way. There are still many problems that occur because of the mu'amalah process in practice. So that the guidelines and order of mu'amalah need to be known and well studied. This research uses the library study method which is carried out by searching for the necessary information through the library materials needed by researchers. Based on the research conducted, it was found that the principles of mu'amalah are the main things that must be fulfilled in carrying out activities related to material rights with fellow human beings. Meanwhile, the limitations are maisir, gharar, haram, riba, and bathil.